The Social Significance of the Cluster in the Economy - Elena M. Kiseleva; Nina N. Danilenko; Amil M. Maharramov; Nadejda N. Martyinenko; Sergey V. Kireev (International Journal of Economics and Financial Issues, 2016)
Transition of the Russian Federation's policy to the innovative way of economic and social development is indispensable imperative to ensure its output to a leading position in the modern globalized world. Among the wide range of means, methods, forms, the mechanisms by which it is possible sharp acceleration of the process of formation of an innovative economy in our country, a special place belongs to the cluster approach. International scientific community is justified, and the practice of developed countries proved that the cluster approach to the structuring of the national economy and regional systems are an important source to improve production efficiency, increase its competitiveness, and increase public welfare. Questions of cluster formation and management of the development of the Russian economy in recent years, becomes the subject of numerous studies by Russian scientists - economists. Cluster policies are becoming increasingly recognized in public authorities. Moreover, there are already official documents, which examine the content and direction of the cluster policy. Keywords: society, cluster, economy, innovation, importance, competitiveness JEL Classifications: A19, O35, O30